Educação & ensino de literatura dos povos originários brasileiros - Aires, Viviane Barbosa Rasga (2023)
Universality in literary teaching is directly linked to teacher (self) training. Is the literature of Brazilian native peoples being adequately worked on in the classroom in order to guarantee this universality and the application of Law 11.645/08? For reasoning we used Kant's concept of literary universality; Paradigms in Literary Teaching, by Rildo Cosson; of Non-Hegemonic Paradigms, by Paulo Freire. As a methodology, we used bibliographical research and a semi-structured interview with teachers from the schools involved. The initial hypothesis was that teachers did not receive adequate training in the academic environment regarding this content and were not able to deepen it in isolation, making their work in the classroom very difficult. After analyzing the data, the results obtained confirmed the hypothesis and drew attention to the importance of (self) training and constant teacher training, so that a more up-to-date, modern and inclusive teaching of the literature of native peoples can be promoted, guaranteeing , so that literary and linguistic prejudice no longer exists and that the rights to use language, history, customs, art and literary reading are widely respected.